The factors that influence consumer spending habits at IADA KETARA / Nur Anis Haziqah Ismail - Ismail, Nur Anis Haziqah (2015)
The purpose of this study is to determine factors that influence consumer spending habits at IADA KETARA. The spending habits will keep increasing from every year not only in others country but also in Malaysia. This study is to identify the relationship between independent variables which are consumer income, advertising, price of goods and services, consumer debts and factor to the dependent variable which is influence spending habit. This study also is to determine the most significant factor that influence consumer spending habits. This study were found that all the independent variables have significant and positive relationship with the dependent variables and consumer income is most significant factor that affecting consumer spending habit at IADA KETARA. Future research is proposed to determine the others factors such as social factors, economic factor, culture factors and which affecting to the consumer spending habits.